River discharge measurement at South African compound weirs in rivers with sediment loads : the development of an improved method for measurement - Lotriet, H. H.(Hugo Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1996.